A theory on political violence in hybrid regimes: insights from Colombia - Cendales, Andrés; Guerrero-Sierra, Hugo; Oñate, Laura (Frontiers in Political Science, 2024)
IntroductionThis article presents a model of political competition in which political parties, through clientelism strategies, vie for control of legislative seats. Parties exercise political violence to prevent potential rivals from gaining power and threatening their position within the hybrid political regime. The theory suggests that the degree of political violence exerted by parties in hybrid regimes will increase (decrease) as they concentrate more (less) power in the legislature.MethodsUsing the methodology of analytical narratives, we examine the narrative on political violence in the Colombian political regime to identify key actors, strategies, information sets, and institutional changes. From these identified elements, we construct a theoretical model of political competition within the mathematical theory of games to explain the institutional changes highlighted in the narrative. Finally, we develop an econometric model to find statistical evidence supporting the predictions of the theoretical model derived from the narrative.ResultsThe narrative and the analytical narrative indicate that, in a hybrid regime, a higher degree of political power concentration causes a higher rate of political violence. The estimation of the Vector Auto-regression model allows us to analyze the response of the violence rate to a shock in the concentration index. Following an unexpected increase in the concentration of political power, the violence rate shows an initial increase of approximately 0.3 percentage points above its initial value. Subsequently, the effect attenuates slightly and stabilizes at around 0.2 percentage points above the baseline, maintaining this level throughout the period.Discussion/ConclusionThe theoretical model proposed in this paper suggests an explanation of political violence that diverges from the explanations offered by traditional theories. We suggest that the theoretical model proposed here captures the historical logic of the relationship between violence, political clientelism, and exclusion in Colombia, a country with a relatively long tradition as a formal democracy (since 1958), leading us to interesting conclusions that have not been proposed so far in the literature on violence in Latin America.